Ultrasonic Extraction of Antioxidants and Anthocyanins from Different Species of Wild Hawthorn Fruit - Sahni, Mahsa; Ghavidel, Reihaneh Ahmadzadeh; Afshar, Sodabeh Ein (Asian Journal of Biological and Life Sciences, 2015)
The hawthorn is a fruit with antioxidant properties that make this fruit useful for the treatment of many diseases. In this study twelve hawthorn species were assayed for their antioxidant capacities evaluating total phenolic compounds, ferric reducing antioxidant power and anthocyanin content. In addition, these extraction methods (cold solvent, cold solvent plus sonication for 5 min and cold solvent plus sonication for 10 min) were investigated. The results from this study thus indicate that there is a significant difference between hawthorn species in terms of antioxidant activity, total phenolic compounds, ferric reducing antioxidant power and anthocyanin content. The C. pentagyna Sub sp. pentagyna species were known as the best species in terms of antioxidant capacities. In addition, the results demonstrated that sonication for 5 min could enhance the level of antioxidant compounds in hawthorn fruit extracts and save extraction time.
Keywords: Antioxidants; Hawthorn; Phenolic compounds; Ultrasonic